Effect of dispersants on the kinetics of asphaltene settling using turbidity measurement method. (17th July 2016) - Shadman, M. M.; Vafaie-Sefti, M.; Ahmadi, S.; Assaf, M. A.; Veisi, S.
ABSTRACT: Organic deposition especially asphaltenes in reservoirs, wells, and equipment has a detrimental effect on petroleum economy. Generally, for chemically control of asphaltene precipitation using dispersants and inhibitors of precipitation or solvents of asphaltene is very common. Although asphaltene in crude oil is stable under specific conditions, but there is no assurance that the system will be stable and asphaltenes could be remaining in suspension state. In this study, the kinetic effects of three dispersants on stabilization of asphaltene aggregates were investigated by turbidity measurement method. Turbidity measurement showed as the dispersant strength rises, the turbidity of unstable sample containing dispersant less declines versus time. In order to carry out further studies on dispersants, the effect of dispersant on asphaltene particle size distribution was investigated. The results of asphaltene particle size distribution measurements showed that adding dispersant cause to decrease the volume percent of particles with medium diameter.